'Zio' Is the New 'N-Word': The anti-Semitic slur is becoming as acceptable as the racial epithet once was. - Kaufman, David Christopher (Commentary, 2026)
The article focuses on "Zio" which has become a standard slur for those who affirm Israel's right to exist as both a sovereign state and Jewish nation. Topics discussed include how "Zio" has been compared with the N-word, how "Zio" is being considered as a charge that could result in the accused being sentenced to death and the diminutive formulation of the word.